The Role of Nurses in Managing Dyspnea in Advance Lung Cancer Patients - Sangchan, Pheerapha (Siriraj Medical Bulletin, 2025)
Dyspnea is a common symptom in advanced lung cancer patients, which can be found in 75-90 percent of patients in the final stages of life. It is a symptom that varies depending on the perception and experience of each patient, resulting in patients managing the symptoms differently and having a direct impact on their physical, mental, and social quality of life. Therefore, the recognition and assessment of dyspnea must be accurate from both the patient’s and the multidisciplinary team’s perspectives. Nurses, as close caregivers, play an important role in assessing symptoms, alleviating symptoms, and supporting patients’ self-management, both in terms of medication and non-drug use, by applying the Symptom Management Theory (SMT) of Dodd et al. through 3 main components: patient’s symptoms experience (Symptom Experience), symptom management (Symptom Management Strategies), and outcomes (Outcome). This article presents international standard guidelines and the latest best practices in caring for lung cancer patients with dyspnea, Nurses play a crucial role in providing advice to patients, to ensure they can lead quality lives even in the late stages of their disease. They can enjoy a high quality of life, choose medication- and non-medical-based symptom management options appropriate for their individual symptoms, alleviate suffering, and live happily under their own health conditions.